Haploinsufficiency of the STX1B gene is associated with myoclonic astatic epilepsy. (May 2016) - Vlaskamp, Danique R.M.; Rump, Patrick; Callenbach, Petra M.C.; Vos, Yvonne J.; Sikkema-Raddatz, Birgit; van Ravenswaaij-Arts, Conny M.A.; Brouwer, Oebele F.
Abstract: We describe an 18-year-old male patient with myoclonic astatic epilepsy (MAE), moderate to severe intellectual disability, behavioural problems, several dysmorphisms and a 1.2-Mb de novo deletion on chromosome 16p11.2. This deletion results in haploinsufficiency of STX1B and other genes. Recently, variants in the STX1B gene have been associated with a wide spectrum of fever-related epilepsies ranging from single febrile seizures to severe epileptic encephalopathies. Two previously reported patients with a STX1B missense variant or deletion were diagnosed with MAE. Our observation of a STX1B deletion in a third patient with MAE therefore supports that STX1B gene variants or deletions can be involved in the aetiology of MAE. Furthermore, STX1B encodes for syntaxin-1B, of which interaction with the protein encoded by the STXBP1 gene is essential for the regulation of the synaptic transmission of neurotransmitters. STXBP1 gene variants have been identified in patients with many different types of epilepsy, including Dravet syndrome and epileptic encephalopathies, suggesting STX1B plays a similar role. We recommend that analysis of STX1B should be considered in the diagnostic work-up of individuals with MAE. Highlights: Third patient with myoclonic astatic epilepsy (MAE) and STX1B deletion or variant. STX1B interacts with STXBP1, which is associated with a spectrum of epilepsies. STX1B gene analysis should be considered in the diagnostic work-up of MAE individuals.